KITAB SUNAN IBN MĀJAH (Biografi, Sistematika, dan Penilaian Ulama) - Nurkholijah Siregar (Hikmah, 2019)
Ibn Mājah is known as someone who is an expert in the fields of hadith, tafsir, and history (Muhaddith, Mufassir, and Mutarrikh). Ibn Mājah with his famous book, sunan Ibn Mājah, is included in the ranks of the Kutubut Sittah. This book with a fiqh style is certainly a distinctive feature and a special advantage for special readers who study fikih and Ushul fikih. The presence of the book of hadith is certainly very useful for the benefit of the people. Its presence is certainly very a reference for Muslims in worship, prayer. But even so it cannot be concealed that this book is still contained in the traditions of the dead, it can even be denied that there are false traditions. But the advantages of Ibn Majah still provide comments on the quality of the hadith. In other words he did not open the Muslims to consume the Hadith without being filtered before.